TINJAUAN YURIDIS TERHADAP PEMIDANAAN PELAKU TINDAK PIDANA PEMASUNGAN ORANG DENGAN GANGGUAN JIWA BERDASARKAN HUKUM PIDANA INDONESIA - Donal, Roy Fran; Indra, Mexsasai; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
problem of shackling is a part that cannot be lost in Indonesian society. People with mental disorders are often victims of shackling, which is generally carried out by their own families. Even though people with mental disorders should be given love and comfort. However, when people with mental disorders are shackled, it will make them feel alone and stressed out. Shackling is done by shackling people with mental disorders using wood with a hole and then sandwiching them on the feet, hands and neck so that the person in shackles cannot move from their place. Shackling is clearly a crime and punishable. This has been stated in article 333 of the Criminal Code regarding deprivation of liberty.This type of research is normative legal research, namely using literature study to search the data. This research is descriptive in nature which tries to provide data as accurate and detailed as the existing problems. In writing this study using qualitative data analysis which means explaining and concluding about the data that has been collected by the author. This research uses secondary data or codified scientific data.The result of this research is to explain that in fact there are weaknesses in the criminal law in acting on the perpetrators of this lockup. The prohibition on confinement is contained in Article 86 of the Law on Mental Health, however this article does not explain the criminal sanctions so it refers to Article 333 of the Criminal Code. In the description of article 333 of the Criminal Code, it does not classify what kind of deprivation of liberty. Deprivation of freedom according to S.R. Sianturi is done with physical restraint. Meanwhile, according to R. Soesilo said that the deprivation of freedom did not have to be physically restrained. Then in the Supreme Court Decision Number 233K / Pid / 2013 it explains that there is no need for physical restraint, so that if article 333 of the Criminal Code is linked to confinement, it is not appropriate. Because people with mental disorders have experienced physical restraint. For this reason, it is necessary to have laws and regulations that provide information on article 333 of the Criminal Code and state it firmly.Keywords: Criminalization - Confinement Perpetrators – People With Mental Disorders.